Orthostatic hypertension as a risk factor for age-related macular degeneration: Evidence from the Irish longitudinal study on ageing. - Mc Garrigle, Christine; Kenny, Rose (My University, 2018)
Purpose: Age related macular degeneration (AMD) is a leading cause of irreversible visual loss in developed countries. It is associated with vascular risk factors including hypertension. Dysregulated blood pressure (BP) behaviour including orthostatic hypertension (OHTN), hypotension (OH) and BP variability (BPV) are associated with end-organ damage, particularly in the brain. We investigated if abnormal orthostatic BP (OBP) was a risk factor for AMD, for which a vascular aetiology is implicated. Methods: A nationally representative, cross-sectional study was carried out 2009/2010 in The Irish Longitudinal Study on Ageing (TILDA). Beat-to-beat BP data, measured by digital photoplethysmography during active stand, was used to characterise OBP behaviour in the 30–110 s after standing. OH, OHTN, BPV and normal stabilisation recovery phenotypes were defined. AMD was identified following masked grading of 45° monoscopic colour retinal photographs, which were centred on the macula and taken with a NIDEK AFC-210 non-mydriatic auto- fundus camera. The relationship between OBP recovery phenotypes and AMD in 3750 adults aged ≥50 years was investigated using multivariate logistic regression models, adjusted for traditional AMD risk factors. Results: From 30 to 110 s post active stand, systolic and diastolic OHTN was associated with increased odds of AMD after adjustment for demographics, health behaviours including smoking, family history of AMD, self- report (SR) diabetes, SR cataracts, objective hypertension and prescribed antihypertensives. No evidence of heterogeneity of OHTN effect was found between those who were hypertensive to those who were normotensive. Conclusions: This study provides evidence that OHTN may be an independent cardiovascular risk factor for AMD.
PUBLISHED
Keywords: Age-related macular degeneration; Orthostatic hypertension; Hypertension; Pathogenesis; Risk factors; Ageing